ADJEKTIVA BERTARAF DAN TAKBERTARAF DALAM BAHASA MAANYAN - Dwiani Septiana (Balai Bahasa Kalimantan Tengah, 2016)
The purpose of this research is to describe adjectives in Maanyan languageusing theory of adjectives from Hasan Alwi. The data for this study aresentences in Maanyan language containing the element of adjectives. Thedata were obtained from observation with recording and noting thesentences. The data were analyzed with agih method and several advancedtechniques such as vanishing, replacing, expanding, and mark readingtechniques. The results indicate that there are degrees of adjective inMaanyan language.